1997
DOI: 10.1103/physrevlett.79.4546
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Strongly Delocalized Atomic States in the5sPhotoionization of Xenon

Abstract: The photoionization (PI) of the Xe atom was investigated in the vicinity of the 5s-shell threshold by photon-induced fluorescence spectroscopy. The highest resolution so far attained of 2 meV enabled us to observe a new series of resonance structures in the 5s-PI cross section closely above threshold. Calculations of the partial 5s-and 5p-PI cross sections were performed taking into account manyelectron correlations. These structures were related with strongly delocalized f-resonances which affect the 5s-PI cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…High-resolution investigations of the energy dependence of the ns-subvalence shell PI CS of rare gases have already shown that the 3 m NIM-2 beamline at BESSY I provides a very narrow bandwidth of the exciting radiation [24,25] and is thus very useful for investigating the predissociation of vibrational FS levels.…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution investigations of the energy dependence of the ns-subvalence shell PI CS of rare gases have already shown that the 3 m NIM-2 beamline at BESSY I provides a very narrow bandwidth of the exciting radiation [24,25] and is thus very useful for investigating the predissociation of vibrational FS levels.…”
Section: Methodsmentioning
confidence: 99%
“…Adapted from (Schartner et al, 1988b(Schartner et al, , 1990aSukhorukov et al, 1992). (Schartner et al, 1989;Schmoranzer et al, 1997b).…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…The ab initio technique described in section 3.3.2 has been widely used in calculations of energy levels of the Rg II ions near the subvalence threshold. Energy levels stemming from ns 1 np 6 and ns 2 np 4 mℓ configurations have been investigated for Ar (n = 3) in (Sukhorukov et al, 1992;Lagutin et al, 1999;Kammer et al, 2006), for Kr (n = 4) in (Schmoranzer et al, 1993;Sukhorukov et al, 1994b;Lagutin et al, 1994;Demekhin et al, 2005;Sukhorukov et al, 2007), and for Xe (n = 5) in (Lagutin et al, 1996;Schmoranzer et al, 1997b;Ehresmann et al, 2010). All these papers contain also original measurements performed by PIFS.…”
Section: Energy Level Calculationsmentioning
confidence: 99%
See 2 more Smart Citations